2014
DOI: 10.1016/j.cbpa.2014.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Chickens from lines artificially selected for juvenile low and high body weight differ in glucose homeostasis and pancreas physiology

Abstract: Early pancreatectomy experiments performed in ducks and pigeons at the end of the 19 th century revealed that avians, unlike mammals, do not display signs of diabetes. Relative to mammals, birds are considered hyperglycemic, displaying fasting blood glucose concentrations twice that of a normal human. While circulating levels of insulin are similar in avians and mammals, and structure and function of the insulin receptor are also conserved among vertebrate species, birds do not experience deleterious effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 68 publications
2
22
2
Order By: Relevance
“…However, it is also possible that consistently low resource availability on the island is reducing the blood glucose levels through plasticity. Considering the divergence time estimates of 9000–34,000 years, and the consistently low levels across all 3 years, and all three species on the islands, we believe the most likely explanation is that the island habitat has selected for convergent low glucose set points in each of these dwarf populations, similar to what has been demonstrated in dwarf laboratory mice (Borg et al., ; Hauck et al., ), artificial selection on chickens for body size (Smith et al., ; Sumners et al., ) and body type among cattle breeds (Bossaert et al., ; Coleman, Chase, Riley, & Williams, ).…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…However, it is also possible that consistently low resource availability on the island is reducing the blood glucose levels through plasticity. Considering the divergence time estimates of 9000–34,000 years, and the consistently low levels across all 3 years, and all three species on the islands, we believe the most likely explanation is that the island habitat has selected for convergent low glucose set points in each of these dwarf populations, similar to what has been demonstrated in dwarf laboratory mice (Borg et al., ; Hauck et al., ), artificial selection on chickens for body size (Smith et al., ; Sumners et al., ) and body type among cattle breeds (Bossaert et al., ; Coleman, Chase, Riley, & Williams, ).…”
Section: Discussionmentioning
confidence: 61%
“…Research on the evolution of body size on islands has largely focused on ecological selective forces for body size evolution (Case, 1978;Lawlor, 1982;reviewed in Whitakker & Fernández-Palacios 2007), and the physiological differences associated with alterations in island body size have not been hitherto investigated. Divergence in physiological mechanisms regulating body size between island and mainland can be predicted to have occurred as they have in laboratory model organisms and agricultural species artificially selected for body size (Borg, Brown-Borg, & Bartke, 1995;Hauck, Hunter, Danilovich, Kopchick, & Bartke, 2001;Smith, Prall, Siegel, & Cline, 2011;Sumners et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It showed that the difference in the regulation of blood glucose homeostasis between two breeds may be related to their pancreatic IR levels and fasting insulin levels at the basal state and their different dynamic responses to exogenous insulin. Similarly, hyperphagic low weight chickens successfully return to initial blood glucose levels at 180 min after insulin injection (80 μg/kg weight), whereas hypophagic obese high weight chickens failed to do this 24 . Results suggest that low body weight chickens should have better glucose regulation ability in response to exogenous insulin perturbation.…”
Section: Discussionmentioning
confidence: 98%
“…Oral glucose tolerance tests are used to assess the pancreatic content of insulin and can be used to characterize differences in hyperglycemic response. While investigating glucose regulation, Sumners et al (2014) observed differences in threshold sensitivity to insulin and glucose clearance rates in lines of chickens divergently selected for high and low juvenile (56 day) body weight. Comparisons of glucose tolerance and plasma NEFA concentrations among RJF, LWS selected for > 50 generations for low body weight, and their reciprocal cross may provide insights regarding metabolic responses.…”
Section: Introductionmentioning
confidence: 99%